Cliff-dwelling plants: rare and precious species in harsh habitats - Zhengnan Zhao; Hongyan Sun; Si Liu; Xiao Chen; Shiwei Zhao; Jiangang Zhu (Frontiers in Plant Science)
Cliffs represent unique ecosystems that harbor diverse rare cliff-dwelling plants (CDPs), which play critical roles in enhancing biodiversity and maintaining ecological stability. Despite substantial advances in CDP research enabled by modern biological technologies, particularly in diversity assessment, taxonomic classification, and conservation strategies, the field lacks comprehensive syntheses of recent progress, impeding efficient identification of emerging research directions. This review systematically examines five key research domains: (1) The ecological and potential application value of CDPs; (2) cliff habitat ecology, focusing on abiotic factors such as microclimate, edaphic properties, and water conditions, as well as biotic components; (3) adaptive strategies of CDPs, encompassing morphological specializations, physiological resilience mechanisms, early growth stage, reproductive characteristics, molecular-level evolutionary adaptations, and genetic diversity patterns; (4) technological advancements in cliff research methodologies; and (5) CDP conservation strategies by conducting a comparative analysis between in situ protection measures and ex situ preservation approaches. Our review reveals three critical research gaps demanding immediate attention: the need for long-term ecological monitoring of cliff habitats and their microenvironmental dynamics, the imperative to understand CDPs’ physiological adaptations to extreme environments, and the necessity to elucidate molecular mechanisms governing plant-environment interactions within these unique ecosystems. Future research should prioritize the development of innovative tools, advanced technologies, and interdisciplinary methodologies to fill in existing knowledge gaps in the field. Such comprehensive efforts will not only elucidate the complex adaptation mechanisms of CDPs but also provide a scientific foundation for their effective conservation and ecosystem management.